Kreatif dengan Canva: Pelatihan Desain Grafis Untuk Peningkatan Kemampuan Berkomunikasi Visual - Taufiq Timur Warisaji; Ulya Anisatur Rosyidah (Jurnal Pengabdian Literasi Digital Indonesia, 2024)
The use of graphic design in communication is becoming increasingly important in this digital era. Visual communication skills are not only needed in the professional world, but also in everyday life. Therefore, this community service activity aims to improve the visual communication skills of MTs Sunan Ampel Jember students through graphic design training using the Canva application. The training was held in three interactive sessions involving students and teachers as participants. The training material includes the basics of graphic design, designing posters and creating attractive presentations using the Canva application. The results of this activity showed a significant increase in the understanding and application of graphic design concepts by participants. Participants are able to create attractive and informative designs for various purposes, both in academic and extracurricular contexts.